2014
DOI: 10.1002/cmdc.201400034
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and DNA Cleavage Activity of Bis‐3‐chloropiperidines as Alkylating Agents

Abstract: Nitrogen mustards are an important class of bifunctional alkylating agents routinely used in chemotherapy. They react with DNA as electrophiles through the formation of highly reactive aziridinium ion intermediates. The antibiotic 593A, with potential antitumor activity, can be considered a naturally occurring piperidine mustard containing a unique 3-chloropiperidine ring. However, the total synthesis of this antibiotic proved to be rather challenging. With the aim of designing simplified analogues of this nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 26 publications
2
51
0
1
Order By: Relevance
“…These observations, and the rapid formation of the reactive species followed by the nucleophilic attack of water, are in good correlation with our hypothesis and with studies on DNA reactivity shown here and in previous paper. 14 Consequently, the present investigations are further supporting our proposed mechanism of reaction. While more work is needed to determine the reactivity in complex biological conditions reflecting in vivo environment, the current studies serve as an experimental model system to demonstrate the efficacy of bis-3-chloropiperidines as DNA alkylating agents.…”
Section: Esi-ms Analysis Of Reactive Aziridinium Ion Formationsupporting
confidence: 81%
See 4 more Smart Citations
“…These observations, and the rapid formation of the reactive species followed by the nucleophilic attack of water, are in good correlation with our hypothesis and with studies on DNA reactivity shown here and in previous paper. 14 Consequently, the present investigations are further supporting our proposed mechanism of reaction. While more work is needed to determine the reactivity in complex biological conditions reflecting in vivo environment, the current studies serve as an experimental model system to demonstrate the efficacy of bis-3-chloropiperidines as DNA alkylating agents.…”
Section: Esi-ms Analysis Of Reactive Aziridinium Ion Formationsupporting
confidence: 81%
“…These data are consistent with our findings in recently published DNA cleavage studies employing a different plasmid (pAT153). 14 Figure 2b and c show the agarose gel electrophoresis pattern for the novel lysine-bridged bis-3-chloropiperidines 1-6. Compounds 1-3 generated single-strand nicks in supercoiled DNA, whereas 4 showed no significant effect (Fig.…”
Section: Bis-3-chloropiperidines Exhibit Dna Nicking Activitymentioning
confidence: 99%
See 3 more Smart Citations